Congenital and genetic disruptions of human ocular motility and alignment – phenotypic / genotypic bi-directional algorithm - Oystreck, Darren T (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.